2021
DOI: 10.2478/msr-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Errors in Active Power and Energy Measurements Under Random Harmonic Distortion Conditions

Abstract: As harmonic distortion of voltage and current is reality in the power system, the need for accurate measurement of electrical power and energy goes beyond the instruments’ specifications and calibration procedures regarding pure sine wave signals. Several international standards and recommendations provide test signals for examination of electricity meters under non-sinusoidal conditions, however, not all of the test signal parameters’ possible states are faithfully represented in those documents. Because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Next, an analysis of the uncertainty intensity in active power measurement will be performed, regarding 2 different approaches. For the concrete performance, voltage and current signals with 230 V and 5 A RMS values and random harmonic distortion [3] are generated from CALMET C300 [14]. The single harmonics' share and phase shifts in relation to fundamentals are illustrated in Table 1.…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Next, an analysis of the uncertainty intensity in active power measurement will be performed, regarding 2 different approaches. For the concrete performance, voltage and current signals with 230 V and 5 A RMS values and random harmonic distortion [3] are generated from CALMET C300 [14]. The single harmonics' share and phase shifts in relation to fundamentals are illustrated in Table 1.…”
Section: Case Studymentioning
confidence: 99%
“…The performance of power and electricity meters, in case of harmonically distorted signals, has been regarded in many scientific contributions [1][2][3][4][5][6]. Measurement errors have been analyzed in relation to different input influence quantities, such as:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in [4] a significant influence of the parameters of measuring transformers on the metering unit operation accuracy was determined, especially when the power factor of load changes. It was also experimentally found that the accuracy of electricity metering is reduced due to the non-sinusoidal nature of load [5], especially in the case of LED lighting [6]. A priori uncertainty estimates may significantly exceed actual values.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In the domain of active electricity meter testing, several international standards [4]- [6], a recommendation [2], and plenty of scientific works [7]- [14] exist, and therefore different examination protocols are established. In the EN 50470-3 standard [6], signals that possess the 5th order harmonics, beside fundamental voltages and currents, are proposed as test conditions for calibration of active electricity meters in non-sinusoidal environment.…”
Section: Introductionmentioning
confidence: 99%